Biorational Management of Gram Caterpillar Helicoverpa armigera (Hubner) In Chickpea Under Organic Farming - Singh, Subash (Indian Journal of Entomology, 2023)
Chickpea is vulnerable to the broad range of insect pests of which the gram caterpillar Helicoverpa armigera is a major pest, and farmers merely rely on pesticides to manage this pest. As pesticides result in many environmental hazards, biorational products are given importance. In this study, Brahamastra and Agniastra @ 10, 15 and 20 litres ha-1 and Neemastra @ 250 litres ha-1 were evaluated against H. armigera in chickpea in 2019-20 and 2020-21. Incidence of H. armigera larvae was significantly less in Agniastra @ 20 litres ha-1 (2.58/ metre plant row) followed by Brahamastra @ 20 litres ha-1 (2.65/ metre plant row) compared to untreated control (3.77/ metre plant row). Agniastra gave maximum pest reduction over control with the least damaged pods. The grain yield was also highest with Agniastra @ 20 litres ha-1 (1011.67 kg ha-1) with economic returns of Rs. 4382.06 ha-1.